Cimifugin ameliorates ulcerative colitis-related lung injury by modulating the JAK1/STAT1 signaling pathway and macrophage M1 polarization - Wang, Guanyuan; Yang, Fan; Zang, Guodong; Shen, Ning; Huang, Lina; Ma, Zhaotian; Li, Ming (Frontiers in Immunology, 2025)
IntroductionUlcerative colitis (UC)-related lung injurys is a commonly overlooked extraintestinal manifestation and there are currently no drugs with definitive efficacy available. Cimifugin has been found to inhibit aberrant inflammation and oxidative stress, but its efficacy in UC-related lung injurys has not yet been demonstrated.MethodsThis study explored the effects of Cimifugin on UC-related lung injurys using RNA-seq in combination with 16S rRNA sequencing.ResultsCimifugin significantly ameliorated symptoms and attenuated colon and lung injury in a UC mouse model, restored the integrity of the intestinal and lung epithelial barriers, and suppressed lung inflammation, which was achieved by inhibiting the JAK1/STAT1 pathway and the M1 macrophage-mediated inflammatory state in the colon and lungs, as well as by improving the homeostasis of the intestinal microbiota. DiscussionCimifugin ameliorates UC-associated lung injury by modulating the JAK1/STAT1 pathway and macrophage M1 polarization.